Prescription of oral short-acting beta 2-agonist for asthma in non-resource poor settings: A national study in Malaysia - Chin, M.C.; Sivasampu, S.; Khoo, E.M. (Public Library of Science, 2017)
Objective Use of oral short-acting beta 2-agonist (SABA) persists in non-resource poor countries despite concerns for its lower efficacy and safety. Utilisation and reasons for such use is needed to support the effort to discourage the use of oral SABA in asthma. This study examined the frequency of oral short-acting Beta 2-agonist (SABA) usage in the management of asthma in primary care and determined correlates of its usage. Methods Data used were from the 2014 National Medical Care Survey in Malaysia, a nationally representative survey of primary care encounters (weighted n = 325818). Using methods of analysis of data for complex surveys, we determined the frequency of asthma diagnosis in primary care and the rate of asthma medication prescription, which includes oral SABA. Multivariate logistic regression models were built to assess associations with the prescription of oral SABA. Results A weighted estimate of 9241 encounters presented to primary care with asthma in 2014. The mean age of the patients was 39.1 years. The rate of oral SABA, oral steroids, inhaled SABA and inhaled corticosteroids prescriptions were 33, 33, 50 and 23 per 100 asthma encounters, respectively. It was most commonly used in patients with the age ranged between 20 to less than 40 years. Logistic regression models showed that there was a higher odds of oral SABA usage in the presence of respiratory infection, prescription of oral corticosteroids and in the private sector. Conclusion Oral SABA use in asthma is found to be common in a non-resource poor setting and its use could be attributed to a preference for oral medicines along undesirable clinical practices within a fragmented health system.